Runaway maids ; Tell me on a Sunday [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
A story of Filipino women working as domestic helpers being retriated. An interview with Monique Wilson during her farewell offering before leaving for London for her theater education.